Gamification in technology and design areas: a teaching innovation project in a fully online environment - Padilla-Zea, Natalia; Verdú, Elena; Baena-Gallé, Roberto (Entertainment Computing, 2025)
Gallifantes and motivation’ is a teaching innovation project intended to foster students to participate in the university online campus of UNIR, a fully online university. Although students at UNIR are used to studying in an online independent way, it is well known that having a learning community and a confident-based relationship with mates enhance learning results. Intended to promote a lively interaction between students, both in the forums and in synchronous lessons, this teaching innovation project proposes gallifantes-rewarded actions during the semester in a competitive run. The 4 students with the highest numbers of gallifantes obtain 0.25, 0.5, 0.75 and 1 additional points in the final grade. In this paper, we present the different approaches followed in 3 subjects in the areas of technology and design, having a total number of 114 active students and 1164 gallifantes rewarded. The students answered a survey at the end of the process. As a conclusion, most of them supports the initiative, obtaining good results in satisfaction, motivation and engagement, while also suggesting improvement opportunities.
Keywords: gamification; engineering education; engagement; educational technology; higher education; motivation